EFFECT OF HYPROLA (HYPNOBREASTFEEDING AND LAVENDERAROMATHERAPY) ON BREAST MILK FLOW IN POSTPARTUM MOTHERS - Ariu Dewi Yanti (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Breast milk is the optimal source of nutrition for infants; however, exclusivebreastfeeding rates in Indonesia remain suboptimal. One of the mainchallenges during the early postpartum period is inadequate breast milk flow,which is often associated with maternal anxiety and insufficient stimulation ofprolactin and oxytocin hormones. Non-pharmacological interventionsfocusing on maternal relaxation may support lactation. This study aimed toexamine the effect of HYPROLA therapy, a combination ofhypnobreastfeeding and lavender aromatherapy, on breast milk flow inpostpartum mothers.This study employed a pre-experimental one-grouppretest–posttest design involving 15 postpartum mothers within 2–7 days afterdelivery. Participants were selected using total sampling. HYPROLA therapywas administered according to a standardized protocol. Breast milk flow wasassessed before and after the intervention using an observation sheet andquestionnaire. Data were analyzed using the Wilcoxon signed-rank test with asignificance level of 0.05.The results showed a significant improvement inbreast milk flow following the intervention. Before HYPROLA therapy, only13.3% of participants experienced smooth breast milk flow, whereas after theintervention, 93.3% demonstrated smooth milk flow (p = 0.001).In conclusion, HYPROLA therapy significantly improves breast mil